Dinamika Psikologis dan Strategi Koping pada Korban Perselingkuhan dalam Pernikahan - Syam Syahrul Dwi Gandana; Teguh Febryanto P. Mangawe; Tys’a Ramadhani; Wafiy Adzkia Susilowati (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Infidelity in marriage is a complex phenomenon that affects individuals’ psychological conditions and family stability. This study aims to examine the psychological dynamics of infidelity victims, coping strategies used to deal with psychological distress, subjective well-being after the incident, and factors influencing decisions to remain in the marriage. This study employed a Systematic Literature Review (SLR) method by analyzing 30 scientific articles published between 2016 and 2026. The findings indicate that victims experience negative emotions such as anger, disappointment, anxiety, and depression, along with decreased self-esteem and trust in their partners. Coping strategies include both problem-focused and emotion-focused coping with varying levels of effectiveness. Subjective well-being tends to decline initially but may improve over time through adaptation and resilience. Decisions to remain in the marriage are influenced by factors such as children, commitment, social support, and religious values. In conclusion, infidelity has multidimensional impacts, requiring a comprehensive approach to understand and address its consequences.